2021
DOI: 10.1093/nar/gkab670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for bipartite recognition of histone H3 by the PZP domain of PHF14

Abstract: Histone recognition constitutes a key epigenetic mechanism in gene regulation and cell fate decision. PHF14 is a conserved multi-PHD finger protein that has been implicated in organ development, tissue homeostasis, and tumorigenesis. Here we show that PHF14 reads unmodified histone H3(1–34) through an integrated PHD1-ZnK-PHD2 cassette (PHF14PZP). Our binding, structural and HDX-MS analyses revealed a feature of bipartite recognition, in which PHF14PZP utilizes two distinct surfaces for concurrent yet separable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Early mass spectrometry analysis of proteins associated with nucleosomes whose histones presented specific posttranslational modifications demonstrated that PHF14 and HMG20A were among the few proteins excluded from nucleosomes containing the H3K4me3 modification, but associated with H3K4-unmodified nucleosomes ( 59 , 60 ). This is consistent with very recent structural studies demonstrating that a module of PHF14, denoted as the PZP domain (formed by the first PHD and the ePHD domains), reads unmodified histone H3 ( 18 ). Co-purification of PHF14 with nucleosomes containing H2AX ( 61 ), H2A.Z ( 57 , 62–64 ) or macroH2A ( 65 ) has also been reported.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Early mass spectrometry analysis of proteins associated with nucleosomes whose histones presented specific posttranslational modifications demonstrated that PHF14 and HMG20A were among the few proteins excluded from nucleosomes containing the H3K4me3 modification, but associated with H3K4-unmodified nucleosomes ( 59 , 60 ). This is consistent with very recent structural studies demonstrating that a module of PHF14, denoted as the PZP domain (formed by the first PHD and the ePHD domains), reads unmodified histone H3 ( 18 ). Co-purification of PHF14 with nucleosomes containing H2AX ( 61 ), H2A.Z ( 57 , 62–64 ) or macroH2A ( 65 ) has also been reported.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism by which the PHF14/HMG20A complex helps to activate the YAP/TAZ-TEAD targets is unknown. Indeed, as discussed above, the histone binding preferences of PHF14 suggest that the PHF14/HMG20A complex might be associated with poised regions ( 18 ). It is commonly accepted that TEAD factors bind to their DNA targets regardless of the presence or absence of YAP/TAZ coactivators—and therefore also under non-activation conditions ( 48 , 49 , 85 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that patients who manifest phenotypes upon LoF of one PHF14 allele express slightly less PHF14 protein from their WT allele in the brain than those who do not manifest disease. Moreover, putative PHF14 orthologs, such as BRPF1 that also harbors a tandem PHD finger (PZP) domain ( 70 ), could functionally compensate for the loss of PHF14 in mice and humans. In fact, mutations in BRPF1 , including a missense mutation within the PZP domain, also cause syndromic intellectual disability ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the histone methylation-specific recognition sites of PHF14 have remained indeterminate in the past few years. Recently, a study conducted by Zheng et al revealed that PHF14 was able to recognize H3K4me3 and H3R8me2a to exert its repressive functions ( Zheng et al, 2021 ). In colorectal cancer, downregulation of PHF14 could reduce carcinogenesis, and our study also indicated that PHF14 was enriched in tumor samples and was associated with poor prognosis, while the molecular mechanisms were not clear.…”
Section: Discussionmentioning
confidence: 99%